Przenoszenie zmienności między akcjami a indeksem giełdowym na Giełdzie Papierów Wartościowych w Warszawie - Kliber, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper, we use the methods of volatility transmission analysis to conduct Polish stock market research. We try to check out if the volatility shocks are being transferred from market index to individual stock or if this movement has opposite direction. The second question was whether there are some stocks that cause volatility crises in the whole market. To find this out we performed research concerning market index of the Polish stock market and twenty largest companies in this market. We used Markov regime switching models to test if there is transmission from index to stock volatility or from stock to index. We conducted also an input response analysis in the VAR model to find out reactions of volatility. We have found the contagion from index to stock in almost all stocks. In the greater part of the stock we have also found interdependence with the index. The impulse response analysis shows that stocks in the Polish market are sensitive rather to the changes concerning whole market than to the individual shocks. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 166-173